2003
DOI: 10.2527/2003.81102383x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary urea level on digestive function and growth performance of cattle fed steam-flaked barley-based finishing diets

Abstract: Four Holstein steers (282 kg) with cannulas in the rumen and proximal duodenum were used in a 4 x 4 Latin square experiment to evaluate the influence of dietary urea level (0, 0.4, 0.8, and 1.2%, DM basis) in a steam-flaked barley-based finishing diet on digestive function. There were no treatment effects (P > 0.20) on ruminal digestion of OM and ADF. Increasing dietary urea level increased (linear, P < 0.01) ruminal starch digestion. Ruminal degradability of protein in the basal diet (no supplemental urea) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 18 publications
5
64
2
5
Order By: Relevance
“…Cattle were weighed at the start of experiment, at day 35 and before the steers were harvested (day 73). Based that the better responses on microbial duodenal flows and digestible energy of diet was observed only when U and SRU was combined at same proportion (0.80% of each) in diets which proportion of S:ADF is about 4.5 (López-Soto et al 2014) and that previous reports (Milton et al 1997;Zinn et al 2003) have shown that supplemental U has more positive effects on growth performance or dietary energy utilization when the diet contains a ADF ratio of greater than 5.0, thus, to test our hypothesis, four treatments were formulated as follows. The treatment 1 (SRU) consisted in combining U and SRU product (Optigen II; a polymer-coated urea, Optigen, Alltech Mexico, Guadalajara, Jalisco).…”
Section: Animal Processing Housing and Feedingmentioning
confidence: 96%
See 2 more Smart Citations
“…Cattle were weighed at the start of experiment, at day 35 and before the steers were harvested (day 73). Based that the better responses on microbial duodenal flows and digestible energy of diet was observed only when U and SRU was combined at same proportion (0.80% of each) in diets which proportion of S:ADF is about 4.5 (López-Soto et al 2014) and that previous reports (Milton et al 1997;Zinn et al 2003) have shown that supplemental U has more positive effects on growth performance or dietary energy utilization when the diet contains a ADF ratio of greater than 5.0, thus, to test our hypothesis, four treatments were formulated as follows. The treatment 1 (SRU) consisted in combining U and SRU product (Optigen II; a polymer-coated urea, Optigen, Alltech Mexico, Guadalajara, Jalisco).…”
Section: Animal Processing Housing and Feedingmentioning
confidence: 96%
“…It has been observed that in highgrain diets (a starch:ADF ratio of greater than 5.0:1), U can be supplemented at a level 50% higher than the (NRC 1984), EG is the daily energy deposited (Mcal/day) estimated by equation: EG = ADG 1.097 × 0.0557W 0.75 (NRC 1984), and DMI is the average daily dry matter intake (Zinn et al 2008). f Observed to expected dietary NE ratio was computed by dividing NE observed between expected diet NE, which was estimated based on tabular values for individual dietary ingredients (NRC 1996 recommended with positive effects on growth performance or in dietary energy utilization (Milton et al 1997;Zinn et al 2003). One possible advantage to higher U levels in finishing diets might be related to the buffering effects of U as a result of its hydrolysis to CO 2 and NH 3 and the potential buffering effects via ammonia (Galyean 1996), and/or because the synchrony of ruminal degradation rates between feed grade U and starch is maybe more favourable in these types of diets.…”
Section: U and S:adf Ratio Effects On Growth Performance And Dietary mentioning
confidence: 99%
See 1 more Smart Citation
“…For finishing cattle diets using steam-flaked sorghum grain, it seems, overall, that there is no great advantage to using urea as the supplemental nitrogen source. Despite no statistical differences in performance or carcass characteristics in the present study, more work is needed to identify other potential mechanisms responsible for increased performance among different cereal grain diets with urea supplementation [e.g., corn, Milton et al (1997), barley, Zinn et al (2003)]. Cereal grains vary in both ruminal and total tract starch digestion (Galyean and Rivera 2003) with sorghum grain ranking lower than corn, barley and wheat.…”
Section: Methodsmentioning
confidence: 98%
“…A restrição de proteína degradável no rúmen na dieta compromete o ganho médio diário, principalmente pelo menor consumo de matéria seca, pela menor digestão ruminal e menor síntese microbiana (Zinn et al, 2003). A alternativa, no intuito de corrigir esses níveis de proteína, é a utilização de fontes proteicas adicionais, por substituição tanto parcial como total da fonte de nitrogênio da dieta por uma fonte de nitrogênio não-proteico, como a ureia, o que pode reduzir o custo do nitrogênio e da suplementação protéica (Owens & Zinn, 1988).…”
Section: Introductionunclassified